Prevalence of Metabolic Syndrome in Patients with Diabetes Mellitus Type 2 Attending Tribhuwan University Teaching Hospital - Shrestha, Lilee; Sharma, Saroj; Jha, Bharat; Khadga, Prem (Annals of Clinical Chemistry and Laboratory Medicine, 2015)
BACKGROUND: Metabolic syndrome (Met S) is a cluster of biochemical and physical conditions that presage the development of atherosclerotic cardiovascular disease. Its association with diabetes mellitus has long been a topic of study. This study intends to find out the prevalence of Met S in Nepalese population using IDF criteria. METHODS: This cross-sectional study was carried out in department of medicine and department of biochemistry, Tribhuwan University teaching hospital, Maharajgunj, Kathmandu. 204 diabetic subjects, with age ranging between 31 to 80 years and similar number of healthy controls were recruited for study. Demographic, anthopometric and biochemical data were obtained as per preformed profoma. Statistical analysis was done using SPSS statistical software version 17.0. RESULTS: Prevalence of metabolic syndrome in diabetic population was found to be 67.3%, while it was only 7.84% in control group. Prevalence was found to be higher in females compared to males. CONCLUSIONS: Prevalence of metabolic syndrome is significantly higher in diabetic subjects, making them highly prone to the ill effects of cardiovascular diseases.